Tingkat Keberhasilan Reposisi Tertutup pada Fraktur Antebrachii di RS Bethesda Yogyakarta pada Tahun 2007–2013 - Budiman, Johan; Sudharmadji; Hariatmoko; Pinzon, Rizaldy Taslim (PT Dexa Medica, 2020)
Forearm fracture defined as fracture that occurs in the forearm, where the radius and ulna bones are both broken. Forearm fracture is the most common type of fracture that occurs in children and adults. Traffic accident is one of the cause of this fracture. The initial approach in non-complicated forearm fracture is closed reduction with cast immobilization (conservative therapy). The aim of this study is to analyze the success rate of closed reduction of the forearm fracture at Bethesda Hospital of Yogyakarta. The study also examines the relationship between the type of fracture and the related success rate of closed reduction on forearm fracture as well as the distribution of forearm fracture at Bethesda Hospital, Yogyakarta. This is a descriptive study with cross-sectional design. Radiographs and medical records of patients with forearm fracture at Bethesda Hospital, Yogyakarta were analyzed retrospectively in the period of 2007-2013. The measured variables are the change in the degree of angulation, apposition changes, gap occurrences, and the presence of overlap between radiological examinations before and after closed reduction. Medical records are also analyzed after reduction is done. Data is statistically analyzed using Chi-Square method. The result shows that closed reduction of forearm fracture performed by emergency team of Bethesda Hospital Yogyakarta during the period of 2007-2013 was quite successful and there is a significant relationship between the type of fracture with the success rate of closed reduction of forearm fracture (p=0.003). Thus, closed reduction is a mainstay initial approach in the patients with forearm fracture. If it is not successful, then surgery can be performed.